Strategi Peningkatan Motivasi Kerja Guna Meningkatkan Kinerja Setelah Masa Pandemi COVID-19 dan Memasuki Masa Endemi - Anggia Lovika; Setyo Riyanto (Jurnal Ekonomika dan Bisnis, 2022)
Regulations that Indonesia has adopted to reduce the incidence of COVID-19 have a positive impact on the Indonesian state. The decline in the incidence of COVID-19 proves that Indonesia has succeeded in starting the stage of the COVID-19 Pandemic leading to the endemic of Covid-19. One result of the Covid-19 pandemic was a change in the pattern of work activities, which was originally in the office turned into long-distance (Work From Home). Workers do not go to the office on duty and adequately coordinate with the internet network. . At the same time, the problem of the coronavirus began to subside with the vaccination program, and some industries began to pull their employees back into the office. This subject raises pros and cons so that it also affects motivation in work. This research uses a qualitative approach which is a descriptive research method, and my personal instrument researchers, inductive data analysis, descriptive in nature, prioritizing the way to results. The results of the study emphasize meaning rather than abstraction; the information obtained leads to qualitative information. The type of research used in this study is a qualitative descriptive study. The descriptive study lists a target of research in a detailed or profound way. This research is carried out by gathering information Information combined through the library study approach, books, journals, and other data information.